THE RELATION BETWEEN CHARACTERISTICS OF NURSES AND COMPLIANCE TOWARD THE IMPLEMENTATION PREVENTION OF PATIENTS FALLS IN REGIONAL PUBLIC HOSPITAL GOVERNMENT SAMARINDA - milkhatun milkhatun (Jurnal Ilmu Kesehatan, 2019)
Most patient safety standards (IPSG) specifically prevent the risk of falling applied by nurses. One of the internal factors that affect compliance is the characteristics of nurses. This study aims to determine the relation between the characteristics of nurses and adherence in the implementation of prevention of patients falling at Samarinda Government Daera General Hospital. The method used is a descriptive correlation with the cross-sectional approach. The instruments used in this study were questionnaires and observation sheets. The total sample of 51 nurses in nonintensive inpatient rooms with sampling techniques used purposive sampling. The analysis test in this study used Rank Spearman. Based on the results of the Spearman rank test of 4 variables, namely age (p = 0.026, rho = 0.312), gender (p = 0.366, rho = 0.129), education (p = 0.224, rho = -0.173), and work period (p = 0.151, rho = 0.204) there is only 1 variable, namely age, which has a relation with nurse compliance in the implementation of prevention of falling patients. There is a significant relation between the age of the nurse and compliance in the implementation of the prevention of falling patients. There is no relation between gender, education and the duration of employment of nurses with adherence to the implementation prevention of falling patients.